Why Should We Understand Multiple Meanings of ‘Gender Security’? - McLeod, Laura (Journal of Regional Security, 2018)
Research concerned with language and meanings is often thought to be less useful and less policy-relevant than research utilising instrumental approaches. This article explores how a deeper understanding of the variety of meanings about ‘gender security’ in relation to Security Council Resolution 1325 can be useful to practitioners. An analysis of three initiatives related to SCR 1325 in Serbia demonstrates that different post-conflict personal-political imaginations leadtoverydifferentinterpretationsof‘gendersecurity’,shapingthesubsequentpolicydesigned to implement SCR 1325. Investigating how (potentially conflicting) ‘gender security’ policy is made is useful to practitioners as it enables us to go some way towards creating a policy that would be meaningful and significant to all stakeholders.